Evaluation of protein undernourishment on the condylar process of the Wistar rat mandible correlation with insulin receptor expression (Journal of Applied Oral Science, 2015)
The mandible condylar process cartilage (CP) of Wistar rats is a secondary cartilage and acts as a mandibular growth site. This phenomenon depends on adequate proteins intake and hormone actions, including insulin. Objectives The present study evaluated the morphological aspects and the expression of the insulin receptor (IR) in the cartilage of the condylar process (CP) of rats subjected to protein undernourishment. Material and Methods The nourished group received a 20% casein diet, while the undernourished group (U) received a 5% casein diet. The re-nourished groups, R and RR, were used to assess the effects of re-nutrition during puberty and adulthood, respectively. CPs were processed and stained with picro-sirius red, safranin-O and azocarmine. Scanning electron microscopy and immunohistochemistry were also performed. Results The area of the CP cartilage and the number of cells in the chondroblastic layer decreased in the U group, as did the thickness of the CP layer in the joint and hypertrophic layer. Renourishment during the pubertal stage, but not during the adult phase, restored these parameters. The cell number was restored when re-nutrition occurred in the pubertal stage, but not in the adult phase. The extracellular matrix also decreased in the U group, but was restored by re-nutrition during the pubertal stage and further increased in the adult phase. IR expression was observed in all CPs, being higher in the chondroblastic and hypertrophic cartilage layers. The lowest expression was found in the U and RR groups. Conclusions Protein malnutrition altered the cellularity, the area, and the fibrous cartilage complex, as well as the expression of the IRs.